THE IMPACT OF BOARD DIVERSITY ON EARNINGS QUALITY OF INDONESIAN BANKS - Kurniawati, Herni; Jap, Yustina Peniyanti (Graduate Program of Universitas Tarumanagara, 2025)
The aim of the research is to empirically demonstrate how the size of the board, duality, experience, independence, and gender in the board of directors can affect the quality of the profits generated by banks listed on the Indonesian Stock Exchange. The research method used is quantitative description by regressing annual report panel data using eviews 12 software. The sample of the research is a banking company in the period 2019-2022. Research results show that the size/quantity of the Board of Directors can reduce the quality of profits, the duality of the board of directors does not decrease/ improve profit quality, the experience that the board has can improve the value of profit, the independence of the boards of directions does not affect the quality and the gender of bank profits. The implication of this research is to provide input to shareholders to consider the characteristics of the board of directors that they possess can generate reliable/quality bank profits such as the independence of the Board of Directors.